Methodology for quantifying the impact of repurposing existing manufacturing facilities: case study using pulp and paper facilities for sustainable aviation fuel production. (12th May 2022) - Brandt, Kristin; Camenzind, Dane; Zhu, J. Y.; Latta, Greg; Gao, Johnway; Wolcott, Michael
Abstract: Sustainable aviation fuel (SAF) is vital for the reduction of the environmental impact of the aviation industry while decreasing the dependence of the USA on foreign petroleum fuels. To date, SAF, especially from cellulosic feedstocks, have struggled to overcome two barriers: (1) meeting price parity with their petroleum counterparts and (2) the large capital investment required for industrial‐scale biorefineries. Repurposing of industrial facilities has been suggested as a means of addressing both challenges. In this study we look at the financial impact of manufacturing SAF using three repurposing value levels. To demonstrate the application of this methodology, we examine case studies based on a wood‐based alcohol‐to‐jet process. Each level evaluated assumes a different portion of the existing facility is useable. The impact on capital costs and minimum fuel selling price is estimated for generalized case studies as well as for specific case studies spread across multiple regions of the USA. The best economic outcomes are achieved when large‐scale facilities have both inside and outside battery limit assets that can be repurposed. The geospatially explicit variables that have the largest economic impact are feedstock price, feedstock composition, and industrial natural gas price. However, the scale and value of repurposing both outweigh the geospatial variables within reasonable limits. Of the locations studied, the lowest minimum selling price (MSP) of 1.16/L was calculated at the Washington facility, a nearly 19% reduction from a matching scaled greenfield facility, a result of existing equipment and infrastructure reducing total capital investment by one‐third and plentiful feedstock. © 2022 The Authors. Biofuels, Bioproducts and Biorefining published by Society of Industrial Chemistry and John Wiley & Sons Ltd.